1991
DOI: 10.1159/000174760
|View full text |Cite
|
Sign up to set email alerts
|

Seminars in Thrombosis, Thrombolysis and Vascular Biology

Abstract: The vascular endothelium, once believed to act solely as a mechanical barrier is, in fact, the body’s most active paracrine organ serving a vital role in vasomotion and thromboresistance. Vasoactive compounds such as prostacyclin and endothelium-derived relaxing factor maintain coronary blood flow in response to physiologic demands, while their antiplatelet effects act along with tissue plasminogen activator and heparin-like species to prevent local thrombus formation. Structural and functional endothelial abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
1
1
0
2
Order By: Relevance
“…11,12 Maintaining a stable antithrombotic surface is essential for long-term success of a vascular prosthesis, and the best surface is a functional endothelium. 16 As seen in our results, endothelial coverage of the ePTFE graft is not completely confluent; at 12 to 18 months, some areas are lacking an endothelium. This makes the ePTFE surface prone to thrombosis and may explain the lesser patency rate and microthrombi observed in this study.…”
Section: Discussionsupporting
confidence: 77%
“…11,12 Maintaining a stable antithrombotic surface is essential for long-term success of a vascular prosthesis, and the best surface is a functional endothelium. 16 As seen in our results, endothelial coverage of the ePTFE graft is not completely confluent; at 12 to 18 months, some areas are lacking an endothelium. This makes the ePTFE surface prone to thrombosis and may explain the lesser patency rate and microthrombi observed in this study.…”
Section: Discussionsupporting
confidence: 77%
“…The FBs are the main cells in the tunica adventitia. A large number of studies have demonstrated that vascular cells play a critical role in maintaining the normal functions of blood vessels . According to the basic principle of tissue engineering, vascular cells are the initial candidates for vascular regeneration.…”
Section: Terminally Differentiated Vascular Cellsmentioning
confidence: 99%
“…στα κύτταρα Leydig των όρχεων.Δεν είναι πρωτεάση και προωθεί την αδρανοποίηση του παράγοντα Va μέσω της ενεργοποιημένης πρωτεΐνης C, αυξάνοντας τη δυνατότητα σύνδεσης αυτής με τα φωσφολιπίδια.Η διεργασία αυτής της τοπικής λύσεως του θρόμβου επιτυγχάνεται με την δράση του ινωδολυτικού συστήματος, το οποίο είναι αρκετά πολύπλοκο και περιλαμβάνει πρωτεολυτικά ένζυμα και ειδικούς ενεργοποιητές και ανασταλτές(Haudin & Η πλασμίνη, εκτός από τη διάλυση του σταθερού ινώδους και την παραγωγή των παραγόντων αποδομής του, έχει την ικανότητα να διαλύει το ινωδογόνο και να παράγονται έτσι προϊόντα αποδομής του ινωδογόνου, καθώς και να αδρανοποιεί αιμοστατικούς παράγοντες πήξεως και κυρίως τους V και VIII.Ο ρυθμός και η έκταση της ινωδολύσεως ρυθμίζεται από τους φυσικούς ανασταλτές του ινωδολυτικού συστήματος σε δύο επίπεδα. Στο επίπεδο των ενεργοποιητών του πλασμινογόνου διά των αναστολέων του ενεργοποιητή του πλασμινογόνου 1 και 2 (PAI -1 και PAI -2) και στο επίπεδο της πλασμίνης διά της α2 -αντιπλασμίνης (α2 -PI)(Becker , 1991). (Εικόνα 6) Το ινωδολυτικό σύστημα γίνεται καλύτερα κατανοητό εάν κάθε ένα από τα συστατικά του και οι πολύπλοκες αλληλεπιδράσεις τους εξετασθούν χωριστά.ΠΛΑΣΜΙΝΟΓΟΝΟΤο πλασμινογόνο είναι μια γλυκοπρωτεϊνη με ΜΒ : 92.000 daltons και 790 αμινοξέα, η οποία συντίθεται στο ήπαρ, στα σπερματικά σωληνάρια και πιθανώς στους νεφρούς.…”
unclassified
“…Η σύνδεση των ενώσεων όπως το ινώδες, το ινωδογόνο και η λυσίνη, στο ρυθμιστικό τμήμα του ενζύμου, επιδρούν στην καταλυτική θέση της πλασμίνης, αλλάζοντας την στερεοδομή του μορίου της και επηρεάζουν την δραστηριότητα της. Η πλασμίνη ως ένζυμο δρα επί του ινωδογόνου και του ινώδους, αλλά ιδρολύει και άλλους παράγοντες, όπως τον ενεργοποιημένο παράγοντα Hageman (fXIIa), και τους παράγοντες V, VIII, IX, XI(Becker , 1991). i. ΕΝΕΡΓΟΠΟΙΗΣΗ ΤΟΥ ΣΥΣΤΗΜΑΤΟΣ ΙΝΩΔΟΛΥΣΗΣ Η ενεργοποίηση του συστήματος ινωδόλυσης, η οποία ουσιαστικά είναι η ενεργοποίηση του πλασμινογόνου σε πλασμίνη, μπορεί να γίνει μέσω τριών οδών.…”
unclassified